Comparison of Variational and Fractional Variational Iteration Methods in Solving Time-Fractional Differential Equations - Hussain, Eman (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper concerned with study of vartional iteration method(VIM) and fractional variational iteration method (FVIM) to solve time fractional differential equations (FDE’s) . So FVIM is more effective than VIM in solving the FDE’s.